Star Wars : the complete visual dictionary - Luceno, James, 1947-; Reynolds, David West; Windham, Ryder; Fry, Jason, 1969-; Hidalgo, Pablo (DK Publishing, 2018)
"Packed with more than 1,500 stunning images, it showcases major and minor characters (such as Princess Leia and Luke Skywalker), creatures, vehicles, weapons, props, and items of tech in unparalleled detail. Beautiful photography and engaging text written by Star Wars experts examines the finer points of Padmé Amidala's costumes, displays Boba Fett's array of weaponry, studies Darth Vader's armor, and reveals the lesser-known background stories to many of the characters. Find out who Poe Dameron's idol is, discover the tech behind BB-8's rolling motion, and much, much more! Fully updated to include the latest installments of the Skywalker saga--Star Wars The Force Awakens and Star Wars The Last Jedi--this invaluable reference guide incorporates all the latest stories and characters. The definitive companion to the Star Wars movies, Star Wars The Complete Visual Dictionary is a must-buy for the beginner and the die-hard Star Wars fan alike."--Amazon.com.